Pelatihan Budidaya Maggot dalam Peningkatan Kewirausahaan Santri Yayasan Ponpes Syamsul Huda Peresak, Kabupaten Lombok Tengah - Risa Umami; Lutvia Krismayanti (AL HAYAT: Jurnal Pengabdian Masyarakat, 2023)
Waste is material that is thrown away as leftovers from industrial and household production and most of it is organic waste. This rubbish problem also occurs in the Syamsul Huda Peresak Islamic Boarding School environment because of the activities of the students who throw rubbish carelessly, resulting in it piling up and causing an unpleasant odor, and can cause disease. Therefore, training and cultivation of Maggots from organic waste was carried out using the biological agent, namely Black Soldier Fly (BSF). The aim of this service is to improve the education and skills of the students at the Syamsul Huda Peresak Islamic Boarding School in utilizing organic waste to be processed into food factory feed substitutes in the form of maggots. The method used in this service is Community Based Research (CBR), which is a research-based method whose paradigmatic results depend on active community participation. This service is carried out in several stages, namely: laying the foundation, planning, collecting and analyzing information, taking action to find useful results in the use of organic waste and educating students in producing maggots. This training is able to provide education and skills, as well as increase students' income from maggot cultivation activities for entrepreneurship